2020
DOI: 10.1186/s40478-020-00904-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade developmental and epilepsy associated brain tumors: a critical update 2020

Abstract: Brain tumors represent the second most frequent etiology in patients with focal seizure onset before 18 years of age and submitted to epilepsy surgery. Hence, this category of brain tumors, herein defined as low-grade, developmental, epilepsy-associated brain tumors (LEAT) is different from those frequently encountered in adults as (A): 77% of LEAT occur in the temporal lobe; (B): the vast majority of LEAT are of low malignancy and classified as WHO I°; (C): LEAT are often composed of mixed glial and neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(205 citation statements)
references
References 78 publications
4
199
1
1
Order By: Relevance
“…5A). Many intersection DEGs, including CCND1, RAC1, PRKCA, THBS1, and AKT3, have been reported to involve in glioma tumorigenesis [18][19][20][21][22][23] and were further confirmed by RT-PCR in U251-shPNO1 cells (Fig. 5B).…”
Section: Thbs1 Acts As the Potential Target Of Pno1 In The Regulationmentioning
confidence: 69%
“…5A). Many intersection DEGs, including CCND1, RAC1, PRKCA, THBS1, and AKT3, have been reported to involve in glioma tumorigenesis [18][19][20][21][22][23] and were further confirmed by RT-PCR in U251-shPNO1 cells (Fig. 5B).…”
Section: Thbs1 Acts As the Potential Target Of Pno1 In The Regulationmentioning
confidence: 69%
“…GGs typically arise from cortical/juxtacortical regions. GG is the most common tumor in the LEAT family [82]. It predominantly occurs in children and young adults and characteristically present with temporal lobe epilepsy.…”
Section: Plgnts Arising From Cerebral Hemispheresmentioning
confidence: 99%
“…DNT is another cortical/juxtacortical tumor in the LEAT family that typically involves the temporal lobe, with preferential involvement of the mesial temporal lobe, and typically presents with temporal lobe epilepsy [82].…”
Section: Tumors With Fgfr1 Rearrangement Dysembryoplastic Neuroepithementioning
confidence: 99%
See 1 more Smart Citation
“…Glioma is the most common type of primary tumors in the nervous system (1,2). Previous studies have shown that the immune infiltration microenvironment of lower-grade glioma (LGG) was strongly linked with the prognosis of patients (3).…”
Section: Introductionmentioning
confidence: 99%